2007
DOI: 10.2337/dc07-0332
|View full text |Cite
|
Sign up to set email alerts
|

Lower Somatostatin Expression Is an Early Event in Diabetic Retinopathy and Is Associated With Retinal Neurodegeneration

Abstract: OBJECTIVE -To test the hypothesis that a reduction of somatostatin (SST) in the retina exists in patients without clinically detectable diabetic retinopathy and that it is associated with retinal neurodegeneration.RESEARCH DESIGN AND METHODS -Human diabetic postmortem eyes (n ϭ 10) without clinically detectable retinopathy were compared with eyes (n ϭ 10) from nondiabetic donors. SST mRNA (RT-PCR) and SST-28 immunoreactivity (confocal laser) were measured separately in neuroretina and retinal pigment epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
149
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(164 citation statements)
references
References 35 publications
5
149
0
6
Order By: Relevance
“…However, before any microcirculatory abnormalities can be detected, retinal neurodegeneration is already present [1][2][3][4]. In fact, we have detected apoptosis and glial activation, two characteristic features of retinal neurodegeneration, in retinas from diabetic donors, which were free of microcirculatory abnormalities in ophthalmoscopic examinations performed in the 2 years preceding death [5,6]. Therefore, the study of the mechanisms that lead to neurodegeneration and of their effects on essential proteins involved in the visual cycle could be crucial for identifying new therapeutic targets in the early stages of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 87%
“…However, before any microcirculatory abnormalities can be detected, retinal neurodegeneration is already present [1][2][3][4]. In fact, we have detected apoptosis and glial activation, two characteristic features of retinal neurodegeneration, in retinas from diabetic donors, which were free of microcirculatory abnormalities in ophthalmoscopic examinations performed in the 2 years preceding death [5,6]. Therefore, the study of the mechanisms that lead to neurodegeneration and of their effects on essential proteins involved in the visual cycle could be crucial for identifying new therapeutic targets in the early stages of diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 87%
“…In fact, neural apoptosis and reactive gliosis, the hallmarks of retinal neurodegeneration, have already been observed in diabetic donors without microcirculatory abnormalities [7,8]. There are several possible approaches to treating neurodegeneration (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we found that patients with diabetic macular oedema and no significant ischaemia on angiography had lower vitreous SST-28 levels than controls, and that this deficit may be attributable to decreased production by neuroretina and RPE cells due to degeneration. 5,6 Chronic inflammation can cause retinal degeneration. Cytokines with pivotal roles in inflammatory processes such as tumour necrosis factor-a and interferon-g induce apoptosis in RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, we showed that retinal neurodegeneration, which occurs before vascular alterations develop, could be responsible for the decreased SST production in diabetic patients. 5 The aim of the present study was to determine the vitreous levels of SST in patients with chronic uveitic macular oedema (CUMO) and quiescent intraocular inflammation to evaluate whether there is a relationship between SST deficit and the development of this complication. As SST-28 is the main molecular variant in the vitreous fluid 8 it was selected as the best candidate to examine for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation